First we imagine, then, we collaborate : An insight with autistic children / Normaliza Abd Rahim and Nik Ismail Harun - Abd Rahim, Normaliza; Harun, Nik Ismail (Universiti Teknologi MARA Cawangan Pahang, 2006)
This research focuses on the autistic children learning a second language. It investigates the nature, number and balance of interactions of ten children and further investigates the content of discussion and reactions which occurred while they were using the learning approach. The subjects consist of 10 children (7 to 15 years old) with autistism from five schools in Selangor and Negeri Sembilan, Malaysia. The ‘Imaginative Learning Approach’ is introduced to enhance learning the English language and, in turn, encourage subjects in collaborating with their peers. It is found that autistic learners are able to collaborate with peers in the ‘Imaginative Learning Approach’.